Strengthened tuberculosis control programme and trend of multidrug resistant tuberculosis rate in Osaka City, Japan - Nobukatsu Ishikawa; Jun Komukai; Hideki Yoshida; Kenji Matsumoto; Akihiro Ohkado; Akira Shimouchi (Western Pacific Surveillance and Response, 2013)
Osaka City has the highest tuberculosis (TB) notification rates in Japan. In the period 1999–2003, the TB control programme was strengthened, and the Stop TB Strategy was implemented to reduce the number of notified cases. The objective of this study was to assess the effect of these control activities in Osaka City, including the implementation of directly observed treatment (DOT), by analysing TB surveillance and routinely collected data. We reviewed the surveillance data of all sputum smear-positive pulmonary tuberculosis (PTB) cases registered in the Osaka City Public Health Office from 2001 to 2008 and data collected from the routine TB programme. The DOT implementation rate increased from 0% in 2001 to 68% in 2008 for smear-positive PTB cases of the general public and to 61% for all PTB cases of the homeless. The proportion of smear-positive PTB cases that had treatment failure and default combined, declined from 8.0% (52 of 650) in 2001 to 3.6% (20 of 548) in 2006. The proportion of cases among the homeless with previous treatment declined from 28% in 2001 to 15% in 2008. The proportion of cases with multidrug resistant-TB (MDR-TB) among those without previous treatment declined from 1.7% in 2001 to 0.9% in 2008. It is logical that reduction in the failure and default rate would lead to the reduction of cases with previous treatment and TB transmission, including resistant TB, therefore to the reduction of MDR-TB rates.